Julianna Shrode: capstone - Shrode, Julianna, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work explores the two modern facets of design: the digital and the analog. I like to play with the marriage between the screen, and the press, and the movement between the two. My perfectionism in Graphic Design contrasted with the organic nature of Printmaking combine to effectively and entertainingly visually communicate. I use digital processes such as procreate and Adobe Illustrator to create my images. Then, moving into the traditional print space, turning those images into relief carvings and photosensitive exposures. Occasionally, then scanning those prints back into the digital spaces to further manipulate. My goal with any piece I produce is to relay a message to my audience with an aesthetically pleasing approach. I use Printmaking to embrace the imperfections embedded within it and implement that liberty into my design. I believe Printmaking is the predecessor to Graphic Design, and the knowledge of one immensely supplements the other.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design